QUALITY OF LIFE OF PATIENTS PRESCRIBED WITH HERBAL MEDICINE - Dyah Aryani Perwitasari; Nur Mahdi; Mustika Muthaharah; I Nyoman Kertia (Jurnal Farmasi Sains dan Komunitas (Journal of Pharmaceutical Sciences and Community), 2016)
Herbal medicine has been an alternative treatment, instead of modern medicines. However, some of patients could experience adverse drug reaction (ADR) due to the use of herbal medicines. The ADR can decrease patients quality of life (QoL). Objective. This study was aimed to understand the QoL of patients prescribed with herbal medicines. Methods. Patients prescribed with herbal medicines as complementary treatment, in two Public Health Centers of Yogyakarta were recruited. The patients were prescribed with herbal medicines one year before this study was started. Naranjo algorithm was used to identify the ADR. The SF-36 questionnaire was given to the patients as the instrument to measure patients QoL. Results. There were 47 patients participated in this study. Most of the patients are female (62.5%).Ten patients experienced ADR. There are no significant differences between QoL domains in patients experienced ADR and those without ADR. However, the scores of physical function, role physical, general health, social function, role emotional, and mental health in patients without ADR are higher than those with ADR ( p0.05) . Conclusion. There are no significant differences of QoL between patients with and without ADR. In general, the QoL of patients without ADR is higher than those with ADR.